2021
DOI: 10.3390/ani11020581
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of L-Carnitine Supplementation during IVM of Canine Oocytes on Their Nuclear Maturation and Development In Vitro

Abstract: This study aimed to investigate the effect of L-carnitine (LC) supplementation during in vitro maturation (IVM) of canine oocytes on nuclear maturation, fertilization status, and preimplantation development. Cumulus–oocyte complexes (COCs) collected from the ovaries of ovariohysterectomized female dogs were matured in vitro for 72 h in a TCM-199 medium supplemented with (0.1, 0.3, 0.6, 1.0, or 2.0 mg/mL) or without (0.0 mg/mL) LC. Matured oocytes were fertilized in vitro with frozen–thawed spermatozoa, and zyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
5
0
1
Order By: Relevance
“…In this regard, the obtained results indicated that the treatment of normal and EMS-induced immature oocytes with LC during IVM increased the proportion of oocytes that reached the MII stage and reduced oocyte degeneration rate. These results are consistent with prior canine and porcine studies demonstrating that adding LC to the IVM medium improved nuclear maturation and subsequent embryo development following IVF (35,36). In addition, here, LC improved cleavage and blastocyst rates as well as total blastocyst cell numbers when added to the maturation medium of EMS-induced and EMS-free mice.…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, the obtained results indicated that the treatment of normal and EMS-induced immature oocytes with LC during IVM increased the proportion of oocytes that reached the MII stage and reduced oocyte degeneration rate. These results are consistent with prior canine and porcine studies demonstrating that adding LC to the IVM medium improved nuclear maturation and subsequent embryo development following IVF (35,36). In addition, here, LC improved cleavage and blastocyst rates as well as total blastocyst cell numbers when added to the maturation medium of EMS-induced and EMS-free mice.…”
Section: Discussionsupporting
confidence: 91%
“…Oocyte and embryo developmental competence are affected by several factors, such as metabolite composition of culture media, oxygen concentration, time, and temperature (Nagai, 2001). Several studies demonstrated that L-carnitine supplementation to either IVM or in vitro culture (IVC) media had positive effects on early embryo development, and beneficial effects have been reported in cattle , mice (Abdelrazik et al, 2009), pigs (You et al, 2012), camels (Fathi & El-Shahat, 2017), and canines (Moawad et al, 2021).…”
Section: L-carnitine and In Vitro Maturation (Ivm)mentioning
confidence: 99%
“…In camels, supplementation of maturation or culture media with 0.5 mg/ml L-carnitine tended to promote nuclear maturation and increase the number of morulae and blastocysts (Fathi & El-Shahat, 2017). In canines, Moawad reported that adding 0.6 mg/ml L-carnitine during IVM exerted beneficial effects on nuclear maturation, fertilization, and developmental capacity of preimplantation embryos (Moawad et al, 2021). In pigs, the inclusion of L-carnitine (0.5-0.6 mg/ml) brought a significant increase in the rates of oocyte | 679 maturation, cleavage (Tamás et al, 2011), and blastocyst development (Wu et al, 2011;You et al, 2012).…”
Section: Abdelrazik Et Al Challenged Mouse Embryos With Hydrogen Peroxidementioning
confidence: 99%
“…Some authors such as No et al (2018) have used coculture with oviduct epithelial cells to improve maturation rates and have achieved 13% of MII using oocytes recovered from bitches at diestrus and 47% of MII with bitches at estrus. Most reports on canine IVM have been focused on the supplementation of the medium with hormones, such as estrogen, progesterone, follicle-stimulating hormone (FSH), luteinizing hormone (LH), human chorionic gonadotropin (HCG), and L -carnitine ( Moawad et al, 2021 ). The medium TCM-199 is the medium of choice for IVM of most domestic species.…”
Section: Introductionmentioning
confidence: 99%